Feedback Surveys As An Essential Tool In The Current Pandemic Scenario (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Knowing the performance and understanding where one stands and which areas one needs to improve is one of the major aspects of learning and assessment. Feedback surveys helps to achieve this and are useful for teachers, students as well as research scholars for their assessment as well as improvement. My research is based on the survey conducted on a group of research scholars during the period of complete digitisation as a result of lockdown. A feedback survey done on various parameters such as online lectures, webinars, online international and national conferences, online DC meetings, online viva voce, hands on training workshops and research work indicates that most of the scholars prefer to do experimental research in the campus, whereas webinars and conferences are preferred online. The research helped to identify the effects of online learning on LSRW skills. Feedback survey is essential for all stake holders whether its students, teachers or research scholars. It is a revolutionary approach but the feedback survey helps to identify the benefits and limitations. This would serve as a platform to identify what is best for scholars, teachers and students.